Matopiba uma região em desenvolvimento - Oliveira, Lorrany Cantuario de (Universidade Federal do Tocantins, 2021)
This study evaluated the socioeconomic and socio-environmental indicators of the states of Maranhão, Tocantins, Piauí and Bahia that make up the MATOPIBA region between 2000 and 2010, in view of the social and economic inequalities that exist for the local population. Through bibliographical, exploratory, descriptive, explanatory and qualitative research, it was possible to make an analysis detailing the MATOPIBA region, which is considered the new agricultural frontier. Thus, it analyzed how the development of this region took place, the economic, social and environmental impacts of this project, and its impact on the local population. It was also possible to identify the existing disparities in the development of the MATOPIBA region using the theories of Myrdal, Perroux and Hirschman. Development occurs in a heterogeneous way, it can be understood as a process capable of transforming a backward economy into a pulsating and modern economy with improved socioeconomic indicators. For Myrdal, one region depends on another to grow, so when interregional trade benefits the most advanced regions and harms the most backward, it is called the regressive effect, on the contrary it is called the propellant effect, which occurs when the expansion region contributes for the development of the most backward regions, through stimulus of production and employment. For Perroux, the development pole creates an agglomeration effect, when there is an increase in the collective demands of the population, such as housing, transportation, etc. Hirschman says that development occurs as a chain of imbalance, which has induced investments and pressures to choose economic policies that aim to correct them, generating another new stage, the retrospective effect has induced new productive investments in the sectors of input, and the prospective effect provokes new investments in any productive activity. In this work it was verified that the MATOPIBA region before being created had as main characteristic, according to Myrdal's theories, of being a regressive region, however with the creation of MATOPIBA it will tend to be an economically prosperous region. The agglomeration effect of Perroux will occur because it will become an agricultural pole and the effect of Hisrchman back and forth over time will be felt and could bring development to the entire region.